Perspectives and experiences of international students at a Swedish university during the COVID-19 pandemic - Ananmalay, Verushka; Benen, Daniël; Luo, Jiali; Machado Da Silva, Isabel; Smith, Elliot; Taniyama, Tomoyo (Adult Education Discourses, 2022)
The COVID-19 outbreak has had a great impact on our daily lives in many aspects, not least of which includes the education sector. Most governments around the world have decided toclose educational institutions in order to contain the spread of the virus, which has required teachers and students to transform their learning styles from on-campus to online. The previous research reveals that this physical transition from on-campus learning to online learning has brought not only technological considerations, but also changes in students’ experiences, emotions and perspectives, yet few studies have looked specifically into students’ perceptions on their transition to online learning.This qualitative research examines students’ learning experiences of and attitudes towards the transition from campus learning to online learning in the context of COVID-19, by analysing twelve semi-structured interviews with students at a university in Sweden. The interviews were created and conducted by thirteen participant-students, six of whom are also the authors of this research. The data collection, analysis and collaborative writing processes were conducted entirely online. Utilising transformative learning theory, the authors investigated how the participants reflected upon the learning transition and on transforming assumptions and expectations. By examining the interviews through the lens of transformative learning theory, the authors uncovered four important themes: life routine, interaction practices, learning process and self-perception.